Extracorporeal membrane oxygenation outcomes in children with Williams syndrome: a review of the ELSO registry. (May 2022) - Martin, Amarilis; Rycus, Peter T; Farooqi, Ahmad; Dentel, John; Cashen, Katherine
Introduction: Williams syndrome (WS) results from a microdeletion that usually involves the elastin gene, leading to generalized arteriopathy. Cardiovascular anomalies are seen in 80% of WS patients, including supravalvular aortic stenosis (SVAS), pulmonary artery stenosis (PAS), and pulmonary stenosis (PS). Sudden death associated with procedural sedation and in the perioperative period in WS children have been reported. This study aims to describe extracorporeal membrane oxygenation (ECMO) use in WS children, identify risk factors for hospital mortality of WS patients, and compare outcomes between WS children and non-WS children with SVAS, PAS, and PS. Methods: Children 0–18 years-old in the Extracorporeal Life Support Organization (ELSO) Registry with a primary or secondary diagnosis of WS, SVAS, PAS, or PAS were included. Results: Included were 50 WS children and 1222 non-WS children with similar cardiac diagnoses. ECMO use increased over time in both groups (p = 0.93), with most cases occurring in the current era. WS children were younger (p = 0.004), weighed less (p = 0.048), had a pulmonary indication for ECMO (50% vs 10%, p < 0.001), and were placed more on high frequency ventilation (p < 0.001) than non-WS patients. Despite reporting a respiratory indication, most (84%) WS patients were placed on VA-ECMO. There were no significant differences between the two groups in terms of pre-ECMO cardiac arrest, ECMO duration, or reason for ECMO discontinuation. Both groups had a mortality rate of 48% (p = 1.00). No risk factors for WS mortality were identified.